2021
DOI: 10.3390/jpm11060471
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and Diagnostic Biomarkers of Anastomotic Leakage: A Precision Medicine Approach for Colorectal Cancer Patients

Abstract: Development of an anastomotic leak (AL) following intestinal surgery for the treatment of colorectal cancers is a life-threatening complication. Failure of the anastomosis to heal correctly can lead to contamination of the abdomen with intestinal contents and the development of peritonitis. The additional care that these patients require is associated with longer hospitalisation stays and increased economic costs. Patients also have higher morbidity and mortality rates and poorer oncological prognosis. Unfortu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 228 publications
(253 reference statements)
0
27
1
5
Order By: Relevance
“…Meanwhile, biomarkers for early diagnosis of CAL have attracted more and more attention. Cytokines such as IL-1, IL-6, IL-10, and TNF-a are polypeptides with known roles in the immune response (23). Wiik et al (24) reported that the concentrations of all measured cytokines were enormously higher locally at the operative site than in the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, biomarkers for early diagnosis of CAL have attracted more and more attention. Cytokines such as IL-1, IL-6, IL-10, and TNF-a are polypeptides with known roles in the immune response (23). Wiik et al (24) reported that the concentrations of all measured cytokines were enormously higher locally at the operative site than in the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal surgeons are facing a similar situation regarding finding a reliable early detector of colorectal AL. The lack of a clear understanding of the pathophysiology behind AL led to the diversification of the investigated potential biomarkers across broad categories such as those of inflammation, ischemia, and tissue repair [ 11 ]. Although none of the examined biomarkers proved to be the gold standard, CRP shows promising results in contemporary literature [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, las alteraciones en la cicatrización de la anastomosis pueden desencadenar salida de contenido intestinal a la cavidad abdominal, denominado fuga de la anastomosis (FA), que conlleva a graves complicaciones, como peritonitis, sepsis y muerte 2,3 . Debido a su alta morbimortalidad, la FA es la más frecuente y temida complicación del tratamiento quirúrgico del cáncer de colon, asociada en algunos casos a la necesidad de reoperaciones, a estancia posoperatoria prolongada e ingreso a unidad de cuidados intensivos, además de peor pronóstico en la supervivencia libre de enfermedad a largo plazo [4][5][6][7] e incremento de 3 a 4 veces en el costo por hospitalización 8 .…”
Section: Introductionunclassified